PENGARUH RASIO TINGGI-LEBAR (Hw/Lw) TERHADAP KAPASITAS BEBAN LATERAL, DAN POLA RETAK DINDING GESER BERTULANGAN RINGAN AKIBAT BEBAN SIKLIK - Mochammad Surya Budi Utomo; Ari Wibowo; Achfas Zacoeb (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2017)
The shear wall is a vertical structural element of a structural system that serves to withstand lateral loads, whether caused by wind or earthquake. In Indonesia is still often found structural system in old buildings that still use a minimal reinforcement ratio or in this case the lightly shear wall. The lightly sliding wall is believed to have a low lateral load capacity, but in some cases in many countries, the lightweight sliding wall is sufficiently resistant to earthquakes. The height-width ratio is an important aspect in the shear wall structure. Therefore, further research is needed on the effect of high-width ratios. This study discusses the effect of high-width ratios on shear lightly shear walls due to cyclic loads. In this study, the shear wall used as a test specimen with many test specimens was 9 shear wall walls with variations of height-width ratios (2.0, 1.3, and 1.0) or with sizes: (800x400mm), (800x600mm), and (800x800mm) . The test is carried out by providing cyclic load and axial load constant of 3% of axial capacity (Pn) of each specimen until the specimen is collapsed by the drift control method. Data in the form of loads and deviations per cycle are recorded for the analysis of collapse mechanisms. While the picture taken as a reference pattern of cracks. The results of the test show that with increasing height-width ratios can produce the smallest lateral load capacity, or vice versa. The lateral load capacity generated by each test object is SW 2.0 (1), SW 2.0 (2), SW 2.0 (3), SW 1.3 (1), SW 1.3 (2), SW 1.3 (3), SW 1.0 1), SW 1.0 (2), and SW 1.0 (3) are 1593kg, 1503 kg, 1592 kg, 3296 kg, 3388 kg, 3286 kg, 4772 kg, 4771 kg, and 4778 kg. Crack patterns that occur on each specimen have the same result that is the same occurrence of opening (gap opening) at the bottom of the wall.